Grain sorghum response to cover crops under a no-till system - Nielsen, Matthew (Kansas State University, 2020)
Cover crops (CCs) are included in rotations between cash crops for many reasons, including reducing erosion, compaction, and sequestering nutrients for optimal crop performance. The objectives of this study were to i) determine the effects of increasing cropping system intensity on CC biomass accumulation, C:N ratio, and residual inorganic profile nitrogen and ii) determine how intensity effects sorghum (Sorghum bicolor L.) growth, development, and yield in a no-till wheat (Triticum aestivum L.), sorghum, soybean (Glycine max L.) rotation. The experiment was conducted in a randomized complete block design with four treatments: chemical fallow (CF), double-crop soybeans (DSB), double-crop soybeans plus a spring cover crop before sorghum (DSBCC), and a summer cover crop mixture after wheat (CCMIX). Nitrogen (N) rates consisting of 0, 40, 80, 120, and 160 pounds acre⁻¹ were subsurface banded after sorghum planting. Sorghum growth and development were characterized by Canopeo (percent canopy cover) and GreenSeeker (NDVI), from seedling through boot stages, by recording days from planting to half bloom, and by chlorphyll readings (SPAD) at half bloom or early grain fill. Sorghum biomass was sampled after physiological maturity to determine N uptake and yield components. Averaged over three years, summer and fall growth of CCMIX produced the greatest biomass at more than 2,000 pounds acre⁻¹ and had the greatest C:N ratio compared to DSBCC and CCMIX sampled in the spring. Residual inorganic profile N at sorghum planting, when averaged over years, was roughly 26 pounds acre⁻¹ and 13 pounds acre⁻¹ less after DSBCC and CCMIX, respectively compared to after CF and DSB. Including a spring cover crop before sorghum (DSBCC) consistently reduced vegetative growth and development of sorghum.Sorghum growth response to CCMIX was inconsistent depending on year. In 2018, when there was no winter survival of the cover crop, sorghum growth after CCMIX was not different from CF. The CCMIX treatment reduced sorghum SPAD values by 6% and 7% in 2017 and 2019, respectively, and N uptake by 41 and 27 pounds acre⁻¹ in 2017 and 2019, respectively. The spring cover crop immediately before sorghum planting (DSBCC) reduced sorghum biomass by 9% (2017) and 27% (2018) compared to CF, though CF was not different from DSB and CCMIX. In 2019, DSBCC was not different from CF, and sorghum after DSB had 10% greater biomass yield than sorghum after DSBCC. Sorghum grain yield was reduced by more than 50% after DSBCC in 2018 compared to CF, though CF, DSB, and CCMIX were not different. In 2019, sorghum grain yields after CF, DSBCC, and CCMIX were not different, and sorghum after DSB had the greatest yields, 7% more than DSBCC. Including double crop or cover crop in a no-till cropping system slowed early-seasoon growth and development and reduced N uptake of the subsequent sorghum crop but had minimal impact on grain yield with adequate weather conditions. However, a spring-planted CC with substantial biomass accumulation immediately before sorghum planting substantially reduced sorghum yield when spring rainfall was below normal.
Keywords: Grain sorghum; Cover crops; No-till